Language Situation among the Armenians of Baghdad: A Sociolinguistic Study - العبيدي، طيبة عبدالكريم (جامعة بغداد - كلية التربية ابن رشد, 2021)
تبحث هذه الدراسة في الوضع اللغوي للغة الأرمنية بين الأرمن في بغداد. ويتدارس الباحث مواطن اللغة حيث يستخدم الأرمن لغتهم الإثنية فيها والعوامل التي تؤدي إلى استخدام لغتهم الإثنية جنبا إلى جنب مع اللغة العربية. وتستخدم الباحثة استبانة مجتمع الدراسة التي تساعدها في إنشاء ملف تعريف عن المجتمع الأرمني الذي يقدم معلومات عن المجتمع. وتستخدم الباحثة أيضا تستخدم استبانة لغوية اجتماعية، التي تتألف من المعلومات المأخوذة من استبانة مجتمع، للإجابة عن الأسئلة الرئيسة للدراسة. وقامت بتوزيع الاستبانة على 50 مشاركا من مختلف الخلفيات الديموغرافية من المجتمع الأرمني. وتستخلص الدراسة إلى أن أرمن بغداد ما زالوا يحافظون على لغتهم الإثنية ويستخدمونها حصريا في المنزل وفي الكنيسة وفي المناسبات الدينية والاجتماعية. كما وجدت الدراسة أن البيت والأسرة والكنيسة هي أهم العوامل الرئيسية التي تحافظ على اللغة الأرمنية بين المجتمع في بغداد. كما يتوضح أيضا أن العوامل الأخرى التي تحافظ على اللغة الأرمنية هي المدارس والمؤسسات والأحداث التاريخية التي تعيش في ذاكرة المجتمع التي تسهم في الحفاظ على اللغة.
This study investigates the language situation of the Armenian language among the Armenians of Baghdad. The researcher examines the domains of language where the Armenians use their ethnic language and the factors that support them use their ethnic language side by side with Arabic language. The researcher uses a pilot questionnaire that helped her to create a community profile which gives information about the community. She uses a sociolinguistic questionnaire, which is formed by the information taken from pilot questionnaire, to answer the main questions of the study. She distributed the questionnaire to 50 participants from different demographic background from Armenian community. The study concludes that the Armenians of Baghdad still preserve their ethnic language and use it restrictedly at home, church and in social religious events. The study also finds that the home, the family and the church are the major factors that maintain the Armenian language among the community in Baghdad. It also shows other factors that maintain the Armenian language such as schools, institutions, and the historic events that live in the memory of the community that contribute to the language maintenance.
Keywords: اللغة الأرمينية -- المجتمع الأرمني -- علم اللغة الاجتماعي -- مدينة بغداد -- العراق